2018
DOI: 10.4149/km_2018_2_121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microstructure and mechanical properties of titanium alloy sheet using low power Nd-YAG laser welding process

Abstract: In the present investigation, welding of 1 mm thick Ti-6Al-4V sheet has been done by Pulsed Wave (PW) Nd-YAG laser with a variation of laser power from 100 to 400 W and welding speed from 4 to 6 mm s −1. The microstructure and microhardness of the fusion zone indicate that the finely serrated and regular plate-shaped microstructures and the resultant hardness in the welds are the key factors behind the enhanced tensile strength of all joints. The weld bead size increases with decreasing welding speed and vice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Both plate 1 and plate 2 had the α and β phases together. This result is similar to those of reported by [2] and [6]. The appearance of the α+β phases is almost globular, which establishes that the welded joint is ductile.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both plate 1 and plate 2 had the α and β phases together. This result is similar to those of reported by [2] and [6]. The appearance of the α+β phases is almost globular, which establishes that the welded joint is ductile.…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies revealed that α and β are the two phases present in the Ti-alloys. The α-phase is usually characterized as a soft phase whereas the β phase is known to possess high hardness [2,6]. The different types of alloying elements in titanium are classified on the basis of their effects on α-β transformation temperature.…”
Section: Testing and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is lower than that of the FZ. This hardness could be linked to the zones' martensitic microstructure and cooling rate [8,9,22,23]. There is a significant decrease in hardness within the BM, 343 ± 12 HV, compared to the HAZ and FZ.…”
Section: Microhardnessmentioning
confidence: 99%
“…In the present scenario, research on welding and its analysis is still happening. Mostly metals such as Al, Tialloys, and diferent grades of steels have been thoroughly analyzed by the researchers to enhance their application range in industries [6,7]. Te importance of heat treatment to metals has also been extensively discussed to modify the mechanical properties such as strength [8], hardness [9], bending strength [10], toughness [11], and ductility [12].…”
Section: Introductionmentioning
confidence: 99%